Modeling the Use of Mixed Methods–Grounded Theory: Developing Scales for a New Measurement Model. (April 2020) - Howell Smith, Michelle C.; Babchuk, Wayne A.; Stevens, Jared; Garrett, Amanda L.; Wang, Sherry C.; Guetterman, Timothy C.
Mixed methods–grounded theory (MM–GT) has emerged as a promising methodology that intersects the value of mixed methods with rigorous qualitative design. However, recent reviews have found that MM–GT empirical studies tend to lack procedural details. The purpose of this article is to apply the "best practices" for conducting MM–GT in a study designed to develop and then test a theoretical model for how undergraduate engineering students develop interest in the engineering PhD. This study contributes to the field of mixed methods research by (a) illustrating best practices for MM–GT, (b) providing an MM–GT scale development example, (c) demonstrating how an MM-GT scale could potentially bypass exploratory factor analysis and proceed directly to confirmatory factor analysis for testing psychometric properties, and showing how a joint display for data collection planning can be used to strengthen integration in an instrument development study.